Birth Preparedness and Its Association with Skilled Birth Attendance and Postpartum Checkups among Mothers in Gibe Wereda, Hadiya Zone, South Ethiopia. (27th December 2016) - Lakew, Yohannes; Tessema, Fasil; Hailu, Chernet
Abstract : Background . Birth preparedness program was designed to enhance skilled birth attendance and postpartum checkups of women in a developing country to reduce the three delays that lead women and neonates to death and disability. However, the relationship between birth preparedness with skilled birth attendance and postpartum checkups among mothers is not well studied. Therefore this study is intended to assess the association between birth preparedness and skilled birth attendance and postpartum checkups. Methods . A community based cross-sectional study was conducted from March to April 2014. Eight out of 22 Kebeles were selected using probability proportional to size sampling method. Seven hundred and forty-five mothers were selected randomly from the sampling frame, generated from family folders obtained from health posts. Data was collected using pretested questionnaire by face-to-face interview. Data was entered into EpiData version 3.1 database and analyzed by SPSS version 16. Result . Out of 745 sampled mothers 728 (97.7%) participated in the study. One hundred and twelve (15.4%) and 128 (17.6%) mothers got skilled birth attendance and received postpartum checkups for their last child, respectively. Birth preparedness, educational status of women and their husbands, and antenatal care visits of mothers were found to be predictor of skilled birth attendance and postpartum checkups. Mothers well prepared for child birth were 6.7 times more likely to attend skilled birth attendance [AOR = 6.7 (2.7–16.4)] and 3 times more likely to follow postpartum checkups [AOR = 3.0 (1.5–5.9)] than poorly prepared mothers, respectively. Travel time to reach the nearest health facility was found as predictor for postpartum checkups of mothers; mothers who travel ≤ 2 hours were three times more likely to follow postpartum checkups than mothers who travel > 2 hours (AOR (95% CI) = 3.4 (1.5–7.9)). Conclusion and Recommendation . Skilled birth attendance and postpartum checkups were low. Encouraging women to attend recommended antenatal care visits and providing advice and education on birth preparedness and obstetric danger signs are important interventions to increase skilled birth attendance and postpartum checkups.